Citrus - Pérez-Gago, María B.; Palou, Lluís (Elsevier, 2021)
Although citrus fruits are nonclimacteric and have a relatively long shelf life, they may experience important postharvest quality losses if they are not properly handled and stored. Major losses are caused by weight loss, physiological disorders, mainly associated to chilling injury, dehydration and physical rind damage, postharvest decay caused by filamentous fungi, and quarantine pests. Postharvest handling by the industry includes degreening with ethylene, conventional cold storage, application of commercial waxes, often amended with chemical fungicides, and in-transit cold treatments against quarantine fruit flies. Optimum storage conditions (2–13ºC and >90% RH) and duration (1–6 months) are quite variable depending on the citrus species and cultivar. Controlled and modified atmosphere technologies are not commercially used in packinghouses due to the general low tolerance of citrus fruits to low oxygen and/or high carbon dioxide. The development of natural edible coatings and alternative nonpolluting antifungal treatments is currently an active research field.